Importance of studying I.V. Leshko-Popel’s activities for the medical students’ moral education - Semenova L.S. (Medičnì Perspektivi)
This article is about I. V. Leshko-Popel who was a well-known doctor of Yeukaterinoslav in the late XIX century. He was called “the friend of the poor”, “People’s doctor”, “outstanding doctor-man”. He was always and everywhere ready to help selflessly the patient where poor people were waiting for him. Author of this article proposec methods to study I. V. Leshko-Popel’s activities for moral education of medical students.